Heuristic data modeling in information systems - Martin Davtyan (Труды Института системного программирования РАН, 2018)
The paper describes research-in-progress work on information systems that store semi-structured data and use heuristics to make hypotheses about possible data structure. Such systems are intended to be more user-friendly as data formalization is performed by answering simple questions.